USE OF SOME MEDICAMENTS IN THE TREATMENT OF AFFECTED CALVES WITH HYPOMAGNESAEMIC TETANY - RAZZAK AL-AZZAWI , W A (The Iraqi Journal of Veterinary Medicine, 1996)
This trial comprised (28) naturally affected calves with hypomagnesaemic tetany, which were diagnosed clinically and by measuring the serum level of magnesium, calcium, sodium, inorganic phosphorus, potassium and SGOT & CPK enzymes. There were significant decrease (P<0.01) in serum level of magnesium and calcium. While serum potassium and serum enzymes level shown significant increase (P < 0.01) during tetanic attacks. On the other hand serum sodium and inorganic phosphorus level were dropped slightly. Each calf was treated for three successive days with magnesium and calcium salts, with tranquilizers, in addition to sodium chloride for relief of dehydration. With the use of these medicaments as compared to the commerical preparations, the frequency of tetanic attacks decreased gradually then disappeared completely after the completion of treatment.